Alimentación de la vaca en pastoreo. Factores que impactan en la eficiencia del uso de los alimentos - Capelesso, Alsiane Simone (2020)
A central component in the structure of a milk production system is the feeding strategy to be used and associated with this, the profile of the animals adapted to each system. Also, in a grazing dairy system, the distance to the grasslands is frequently viewed as a problem because the cows need to walk long distances to access the pasture every day. In feeding strategies which include pasture from direct harvest, the focus should also be given to the category of animals, since that primiparous dairy cows may be more sensitive to these systems. Therefore, the three experimental works carried out in this thesis intend to characterize how these three imposed factors affect the efficiency of food use testing: (i) Cows of different genetic origin, managed in different feeding strategies on direct grazing; (ii) cows that walking to access to the pasture, and, (iii) primiparous cows that were subjected to a reduction in milking frequency during early lactation. In general, food efficiency was affected by the factors evaluated. As the main results, it was observed that Holstein genetic mainly affected the production variables, and the feeding strategies mainly affected the nutrient consumption and digestibility variables. It was also observed that walking at 5 km/d or fasting for approximately 100 min/d did not affect intake, but behavior, rumen fermentation, and milk production were more affected by fasting than walking. At the same time, cows milked once a day had the same intake compared to cows milked twice, but during the treatment period, milk production was 40% lower in cows milked once a day. In these same animals, the serum concentration of β-hydroxybutyrate was poorly related to energy balance during early lactation. Thus, we synthetically conclude that: (i) the increasing inclusion of grass directly harvested by cows, decreases the feed efficiency for milk production, (ii) fasting during exercise is the main responsible for the decrease in milk production of dairy cows, as a consequence of lower fibrous digestibility, and (iii) cows milked once a day had a decrease of approximately 50% in nutrient-use efficiency for milk production but presented a better energy status. According to the general hypothesis, the factors evaluated in this doctoral thesis affected nutrient-use efficiency for milk production.